Factores de riesgo asociados a resistencia de antimicrobianos en pacientes hospitalizados con infección del tracto urinario del Hospital Regional de Loreto – 2022 - Condori Valverde, Victor Hugo (2024)
Antibiotic resistance has increased in urinary pathogens. In Peru, the common causal agent of urinary tract infection is the Escherichia coli bacterium and it shows BLEE phenotype with an incidence of 31.1 % in adults. Consequently, it is necessary to identify the risk factors that generate antimicrobial resistance in patients hospitalized by urinary tract infection. The following work aim is to evaluate the risk factors associated with antimicrobial resistance, as well as pre-hospitalization antibiotic exposure, urinary tract conditions, previous hospitalizations or associated health conditions in patients hospitalized with urinary tract infection at the Regional Hospital of Loreto during the year 2022. The intention of this analytical observational research project, case-control type, distributed in paired series of 1 case by 1 control, which study population includes hospitalized patients diagnosed by culture and antibiogram of antimicrobial resistant urinary tract infection (case), and hospitalized patients diagnosed by culture and antibiogram of antimicrobial susceptible urinary tract infection (control). With this information, we will be able to identify the risk factors for resistance in hospitalized patients with urinary tract infection at the Regional Hospital of Loreto, with 95% confidence intervals (95% CI).